Analisis Persepsi Masyarakat Desa Laut Dendang Terhadap Sistem Tanggung Renteng PNM Mekaar Dalam Pandangan Ekonomi Islam - Fitri Sagita; Imsar Imsar (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine the effect of public perception related to the decision to use the community on the joint responsibility system. The background of this research is that many people in Laut Dendang Village have joined as members of PNM Mekaar. This research uses quantitative methods. The population in this research amounted to 51 respondents. Collecting data in this study using questionnaires distributed through google forms, interviews, and distributing questionnaires. The results of the data obtained through the distribution of questionnaires and questionnaires were studied using multiple linear regression tests. Data analysis shows that the perception of trust and need has no influence on people's decisions to use the joint responsibility system. The risk and financing variables indicate the number of community decisions to use the joint responsibility system.